Respostas

2014-08-07T14:48:30-03:00
F)  \dfrac{x}{4} + \dfrac{x}{3} =x-100

 \dfrac{3x}{12} + \dfrac{4x}{12} = \dfrac{12x-1200}{12}

\dfrac{7x}{12} = \dfrac{12x-1200}{12}

12x-7x =1200

5x =1200

x = \dfrac{1200}{5}

x=240


g)  \dfrac{4}{5} + \dfrac{3x}{4} = \dfrac{1}{10} +x

 \dfrac{16}{20} + \dfrac{15x}{20} = \dfrac{2}{20} + \dfrac{20x}{20}

\dfrac{15x+16}{20} = \dfrac{20x+2}{20}

15x+16 = 20x+2

 20x-15x=16 -2

5x=14

x= \dfrac{14}{5}


h)  \dfrac{7S}{20} - \dfrac{2S}{5} + \dfrac{S}{4} + \dfrac{3S}{20} = \dfrac{1}{10}

 \dfrac{7S}{20} - \dfrac{8S}{20} + \dfrac{5S}{20} + \dfrac{3S}{20} = \dfrac{2}{20}

 \dfrac{7S-8S+5S+3S}{20}= \dfrac{2}{20}

7S=2

S= \dfrac{2}{7}


i) A IMAGEM APARECE CORTADA!!!


j)  \dfrac{1}{6} - \dfrac{x}{2} =- \dfrac{2x}{3} + \dfrac{1}{4}

 \dfrac{2}{12} - \dfrac{6x}{12} =- \dfrac{8x}{12} + \dfrac{3}{12}

 \dfrac{2-6x}{12} =\dfrac{3-8x}{12}

2-6x =3-8x

8x-6x =3-2

2x =1

x= \dfrac{1}{2}